The Effect of Walking Exercise on Blood Pressure of Older Adults with Hypertension - Mondjil, Rofina; Rahim, Alfyan; Haruna, Sri Rahmah (Omni Nursing Journal, 2024)
Background: Hypertension is one of the diseases that causes the most prominent death worldwide. Most hypertension attacks the elderly. One of the causes of hypertension is a lack of physical activity. Performing regular morning walking exercise may lower blood pressure of patients with hypertension. Objective: This study aimed to evaluate blood pressure before and after performing walking exercise to reduce blood pressure in the elderly with hypertension.  Methods: This study used a pre-experimental design with a pretest-posttest design. The purposive sampling technique was utilized. The sample number was 18 respondents at Antang Health Center.  Results: The study showed that systolic blood pressure before walking exercise was 174 mmHg with a standard deviation of 8.762, and diastolic blood pressure after walking exercise was 75.56 mmHg with a standard deviation of 4.369. The Wilcoxon test showed a value of p= 0.000. This means that there is an effect of walking exercise on reducing systolic and diastolic blood pressure in the elderly.  Conclusion: Walking exercise has an effect on lowering blood pressure in the elderly with hypertension at Antang Health Center.